(untitled) (Journal of Engineering, 2014)
The solar photocatalytic degradation of diuron, which is one of the herbicides, has been studied by a solar pilot plant in heterogeneous solar photocatalysis with titanium dioxide. The pilot plant was made up of compound parabolic collectors specially designed for solar photocatalytic applications. The influence of different variables such as, H2O2 initial concentration, TiO2 initial concentration, and diuron initial concentration with their relationship to the degradation efficiency were studied. Hydrogen peroxide (H2O2) found to increase the rate of diuron degradation. The best removal efficiency of heterogeneous solar photocatalytic TiO2 system was found to be 46.65 % and for heterogeneous solar photocatalytic TiO2/ H2O2 system was found to be 80.65 %. Based on these results, the solar photocatalytic degradation by TiO2/ H2O2 system could be a useful technology for the treatment of effluents containing diuron.